(untitled) - Imakawa, Cibele Santini Oliveira; Nadai, Mariane Nunes; Reis, Monica; Quintana, Silvana Maria; Moises, Elaine Christine Dantas (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To review concepts, definitions, and findings about fear of childbirth (FOC).Methods A bibliographic review was carried out through the main scientific databases in 2020.Results All 32 articles considered potentially relevant were analyzed. A recent study suggests that the global prevalence of FOC can reach up to 14%. Factors such as parity, gestational age, previous birth experience, age and nationality of the woman seem to influence FOC.Conclusion Fear of childbirth could be related to an increased risk of adverse obstetric outcomes such as maternal request for cesarean delivery, preterm birth, prolonged labor, postpartum depression, and post-traumatic stress. These evidence highlight the importance of the discussion regarding this topic.
Keywords: fear; childbirth; obstetric labor; pregnant; delivery